Family-centred care for children with long-term conditions - Coyne, Imelda (Henry Stewart Talks, 2017)
History and evolution of family-centred care (FCC), Defining FCC (Core concepts & Key attributes), Benefits of FCC, Changing roles and relationships, Challenges with FCC, Facilitators of FCC, Strategies for effective FCC, Questions to reflect upon & further research